Effects of Social Participation by Middle-Aged and Elderly Residents on the Utilization of Medical Services: Evidence From China - Liu, Tai-Yi; Qiu, De-Chao; Chen, Ting (Frontiers in Public Health, 2022)
Objectives Aim to evaluate the effect of social participation on utilization of medical services among middle-aged and elderly residents in China. Methods We used data from the 2018 wave of the China Health and Retirement Longitudinal Study. Social participation is classified into three types. Furthermore, to control for confounding factors, our study computed propensity score matching (PSM) to evaluate the effect of social participation on the utilization of medical services. Result The result of PSM indicates that social participation significantly positively affects the utilization of outpatient services, the average treatment effect on the treated (ATT = 0.038***) and the utilization of inpatient services (ATT = 0.015**) by middle-aged and elderly residents. Furthermore, the utilization of outpatient health care services was significantly positively associated with leisure activities (ATT = 0.035***), social activities to help others (ATT = 0.031***), and learning activities to gain new knowledge (ATT = 0.034***) among middle-aged and elderly residents. The utilization of inpatient health care was significantly positively associated with leisure activities (ATT = 0.015***) but had no significant association with social deeds that help others and increased new knowledge among middle-aged and elderly residents. Conclusion Thus, social participation significantly positively affects healthcare utilization by middle-aged and elderly residents. Hence, the government and society should provide more conveniences and promote social participation among middle-aged and elderly residents.